Melusine; or, The Noble History of Lusignan - d'Arras, Jean (Penn State University Press, 2021)
Jean d'Arras's splendid prose romance of Melusine, written for Jean de Berry, the brother of King Charles V of France, is one of the most significant and complex literary works of the later Middle Ages. The author, promising to tell us "how the noble and powerful fortress of Lusignan in Poitou was founded by a fairy," writes a ceaselessly astonishing account of the origins of the powerful feudal dynasty of the Lusignans in southwestern France, which flourished in western Europe and the Near East during the age of the Crusades. The spellbinding story of the destinies of the fairy Melusine, her mortal husband, and her extraordinary sons blends history, myth, genealogy, folklore, and popular traditions with epic, romance, and Crusade narrative.Preceded by a substantial introduction, this translation, the first in English to be amply annotated, captures the remarkable range of stylistic registers that characterizes this extravagant and captivating work